U.S. National Park Service (2006)
Gates of the Arctic National Park & Preserve is an area of superlative natural beauty and exceptional scientific value in Alaska's Brooks Range. The maze of glaciated valleys and gaunt, rugged mountains is cut by wild rivers and covered with boreal forest and arctic tundra. Moose, caribou, Dahl sheep, wolves, and grizzly and black bears inhabit the land.